2011
DOI: 10.1017/s0144686x11000420
|View full text |Cite
|
Sign up to set email alerts
|

Caring for grandchildren and intergenerational support in rural China: a gendered extended family perspective

Abstract: This investigation examines how support from adult children is affected by their parents' involvement in grandchild care. Instead of focusing on dyadic interactions, we adopt a gendered extended family perspective to examine how financial and emotional support from children was influenced when their siblings received help with child care from their elder parents. The data were from a two-wave (2001, 2003) longitudinal study of 4,791 parent–child dyads with 1,162 parents, aged 60 and older, living in rural area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(116 citation statements)
references
References 51 publications
9
107
0
Order By: Relevance
“…In her study on the effects of the onechild policy on filial piety, Deutsch (2006) finds that contemporary single children tend to feel a particularly strong obligation towards their parents. In their research on care practices in Chinese families, Cong and Silverstein (2011) and Chen et al (2011) describe high levels of intergenerational solidarity among their participants, in terms of emotional support, financial assistance, the participation of grandparents in childcare, and so forth.…”
Section: Remaking the Intergenerational Relationships In The Post-maomentioning
confidence: 99%
See 1 more Smart Citation
“…In her study on the effects of the onechild policy on filial piety, Deutsch (2006) finds that contemporary single children tend to feel a particularly strong obligation towards their parents. In their research on care practices in Chinese families, Cong and Silverstein (2011) and Chen et al (2011) describe high levels of intergenerational solidarity among their participants, in terms of emotional support, financial assistance, the participation of grandparents in childcare, and so forth.…”
Section: Remaking the Intergenerational Relationships In The Post-maomentioning
confidence: 99%
“…For the couples we interviewed, their efforts to construct and maintain a viable long-term intimate bond came to be closely entwined with the negotiation of an intergenerational intimate space, against the backdrop of perceptions of significant cultural difference. Whereas filial piety and the everyday practices that are associated with it may continue to be accepted as a matter of course by younger Chinese (Deutsch 2006;Cong and Silverstein 2011), the insertion of a foreign member into a Chinese family opens intergenerational relationships up to scrutiny and questioning, due to sometimes significant differences in understandings of family life.…”
Section: 'They Are Independent Compared To Other Women'mentioning
confidence: 99%
“…Recent studies have highlighted the importance of examining intergenerational exchanges within the larger family context (Bengtson, 2001;Cong & Silverstein, 2011a;Davey et al, 2004;Eggebeen, 1992;Leopold & Raab, 2013;Tolkacheva et al, 2010;Van Gaalen et al, 2008). They have called for an examination of within-family differences and variations in parents' giving among children, i.e., the exchange between the parents and each child in a family rather than the children as an aggregate (Silverstein & Giarrusso, 2010;Suitor, Pillemer, & Sechrist, 2006).…”
Section: The Network Family Approachmentioning
confidence: 99%
“…Although parental provision of socio-emotional support to one child is likely to be enhanced when the parents give support to their other children (enhancement), child-to-parent support decreases when the parents receive support from their other children (compensation) (Spitze, Ward, Deane, & Zhuo, 2012). Cong and Silverstein (2011a) found that in rural China, parents received more emotional support (but not financial support) from their children when the parents provided more childcare for their other children. Mothers may equalize the socio-emotional support given to one child by helping their other children with practical support, or vice versa (Kalmijn, 2013).…”
Section: The Network Family Approachmentioning
confidence: 99%
See 1 more Smart Citation